Pornography and Sexual Deviance : A Report of the Legal and Behavioral Institute, Beverly Hills, California. - Goldstein, Michael J.; Kant, Harold S.; Hartman, John J. (Berkeley : University of California Press, 2022)
Does pornography represent ""a clear and present danger' to our society? This issue is being debated in the courts with increasing frequency, and is intimately tied to the broader issue of censorship and the voiding of first amendment protection which it implies. This volume deals both with the psychological effects of exposure to erotica and with the legal implications of censorship of pornography. This title is part of UC Press's Voices Revived program, whic.
10. THE ROLE OF FANTASY IN THE USE OF EROTICA -- 11. PSYCHOLOGICAL IMPLICATIONS OF THE STUDY -- 12. PORNOGRAPHY AND OBSCENITY: ITS DEFINITION AND CONTROL IN A FREE SOCIETY -- APPENDIX. CLINICAL RESEARCH INSTRUMENT 187 -- REFERENCES -- INDEX
Description based upon print version of record.
JSTOR
Keywords: Pornography; Paraphilias; Pornography -- United States -- Psychological aspects; Erotica -- Psychological aspects; Sex offenders -- Psychology -- Case studies; Pornographie; Pornographie -- États-Unis -- Aspect psychologique; Érotisme -- Aspect psychologique; Délinquants sexuels -- Psychologie -- Études de cas; pornography; Erotica -- Psychological aspects; Paraphilias; Pornography; Pornography -- Psychological aspects; Sex offenders -- Psychology; United States; Case studies